Multinuclear Variable Temperature NMR Studies on Cyanide, Water and Hydroxyl Group Scrambling on Halogenation of K2[Pt(CN)4] and Related Reactions - Javad Sabounchei; Sadegh Salehzadeh (Iranian Journal of Chemistry & Chemical Engineering, 1998)
195Pt and 1H NMR has been used to show that addition of chlorine and bromine to [Pt(CN)4]2_ in presence of perchloric acid in water results in cyanide and water scrambling with formation of eleven complexes of the type [Pt(CN)4-nCl(H2O)n+1](n-1)+ (n=0, 1, 2, 3, 4). Addition of NBu4OH to this solution gives (NBu4)2[Pt(CN)4Cl(OH)]. NMR measurements in acetone also show cyanide and hydroxyl group scrambling with formation of complexes of the type [Pt(CN)4-nCl(OH)n+1]2-, (n=0, 1, 2, 3, 4).